Thermal transport in thin films and across interfaces of dissimilar phase materials - Yu, Kenny (Trinity College Dublin. School of Physics. Discipline of Physics, 2023)
As electronic and photonic devices steadily become more miniaturised and integrated the power density and heat flux that is required is increasing rapidly. Electronic and photonic circuits are now being integrated on the same chip and require very different thermal management strategies. Microscale thermal management solutions such as thin film thermoelectrics, microfluidics, and nanoporous evaporators are now being considered as they can provide tailored localised thermal management at chip level for hotspot control and thermal tuning of optical components. In addition to handling the higher total heat flux, they are also typically designed to handle localised hot spots which cannot be achieved using conventional macroscale solutions. However, information on the electronic and thermal properties of thin films is often required in the development and design of microscale thermal solutions as thin film properties deviate significantly from bulk. Also, a decrease in device size means that the surface-to-volume ratio increases, therefore interfacial properties begin to dominate over the material properties in thermal transport. Therefore, understanding, predicting, and controlling thermal transport through thin films and across interfaces is critical to the advancement of future integrated microscale thermal management solutions. In this thesis we develop a custom non-contact thermal measurement technique known as frequency domain thermoreflectance (FDTR) and apply this to quantify a range of thin films and interfaces of interest to integrated microscale thermal management. The first part of this thesis is centred around the use of FDTR to quantify thermal properties to aid in the development of microscale thermoelectric coolers (?TECs). Using kinetic theory and measured thermal properties, the size effect of an electrodeposited Bi2Te3 thermoelectric film in a development ?TEC test device is investigated. The second part of this thesis focuses on investigating the relationship between thermal transport and wettability across solid-liquid interfaces by using self-assembled monolayer (SAM). The results from FDTR suggest that surface contamination can greatly influence the thermal boundary conductance (TBC), which is beyond being proportional to the thermodynamic work of adhesion. The third and final part of the thesis focuses on investigating the effect of physisorbed contaminant on interfacial thermal transport by using a known species. In additional to the use of FDTR, we develop a continuum theory to aid the investigation. The experimental and theoretical results shows that the effective Au-H2O TBC with a C9H20 interlayer is more than twice lower as compared to Au-H2O without an interlayer. The theoretical model shows that the bonding potential energy of the interlayer does indeed play a dominating role in the effective interfacial thermal transport.
APPROVED
Keywords: frequency domain thermoreflectance; phonon scattering; thermoelectric thin film; solid liquid interface; thermal boundary conductance; thermal conductivity; thermal transport; volumetric heat capacity